Light and Scanning Electron Microscopic Studies on the Reissner's Fibre of the Pig - Kumari, P; Kumar, Pawan (Indian Journal of Veterinary Anatomy, 2012)
Reissner's fibre present in relation to subcommissural organ was studied in 10 adult pigs of non-descript local mixedÂ  breed by light and scanning electron microscopy. The Reissner's fibre was present in mid line towards free ependymal surface and extended throughout the length of subcommissural organ. It was constituted by cilia, microvilli, glycocalyx along with heterogeneous material consisting of RBCs and cellular debris. A positive reaction for PAS and mercury bromphenol blue indicated the secretions to be glycoproteinaceous in nature. Scanning electron microscopy presented Reissner's fibre as a cord like structure which originated from the apical spherical protrusions of the subcommissural organ. The rough and irregular surface of the fibre presented longitudinal and transverse grooves having RBCs and cellular debris of varying shape and size.